Effect of duration of time and dosage on fermentation of cacao pod by using Indigenous Microorganism YL (MOIYL) - Eka Wulandari; Tri Hesti Wahyuni; Hasnudi .; Nurzainah Ginting; Ma'ruf Tafsin (Jurnal Peternakan Integratif, 2019)
The main problem with cocoa pod is the high crude fiber content and lowcrude protein. A treatment needed to change the nutritional content, one of which isfermentation. In this study, fermentation used Indigenous microorganisms which wereYL (MOIYL). This research lasted for 3 months which was carried out from July toSeptember 2018 at the Laboratory of Animal Production and the Laboratory of AnimalNutrition Sciences at the Faculty of Agriculture, University of North Sumatra. Theresearch design used was Factorial 4 x 4 Completely Randomized Design (CRD), with 3replications where factor 1 was the various levels of inoculum of Indigenous YL(MOIYL) and factor 2 was the length of fermentation (incubation) with measuredparameters of crude protein, crude fiber, crude fat, and ash content using proximateanalysis.The results showed that cocoa pod fermentation using Indigenous YL (MOIYL)microorganisms could improve the quality of nutrient content including the highestwater content with a dose of 3% with a 7 day fermentation of 11.75% and the lowestwithout Moiyl with 21 days fermentation time of 10.02%. highest crude protein with 5%dose with 7 days fermentation of 11.89% and the lowest without Moiyl with 28 daysfermentation of 7.18%, highest crude fat at 5% with 7 days fermentation at 1.33% andthe lowest without Moiyl with 28 days fermentation time is 1.22%, while the highestcrude fiber is 5% with 7 days fermentation of 21.3% and the lowest is 5% with 28 daysfermentation of 23.93%, the highest dry matter is 3% with 7 days fermentation timeequal to 88.24% and the lowest without Moiyl with 7 days long 89.95%, highest ashcontent with d osis 1% with a 7 day fermentation time of 9.52% and the lowest ashcontent without Moiyl with a 7 day fermentation time of 11.17%. The results of thisstudy concluded that cocoa pod fermentation using 5% Indigenous YL (MOIYL)microorganisms and 7 days fermentation time could increase water content, crudeprotein, and crude fat, while crude fiber, dry matter, and ash content decreased.